2005
DOI: 10.1021/pr0502471
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Fluorescence Difference Gel Electrophoretic Analysis ofStreptococcusmutansBiofilms

Abstract: Compared with traditional two-dimensional (2D) proteome analysis of Streptococcus mutans grown as a biofilm from a planktonic culture at steady state (Rathsam et al., Microbiol. 2005, 151, 1823-1837), the use of 2D fluorescence difference gel electrophoresis (DIGE) led to a 3-fold increase in the number of identified protein spots that were significantly altered in their level of expression (P < 0.050). Of the 73 identified proteins, only nine were up-regulated in biofilm grown cells. The results supported the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 73 publications
1
34
0
Order By: Relevance
“…In that proteome analysis, performed by Len et al (39) and using conditions of acid stress, several genes involved in branched-chain amino acid biosynthesis were upregulated at pH 5.0, including ilvC, encoding a keto acid reductoisomerase, and ilvE, encoding a branched-chain amino acid aminotransferase. Two-dimensional fluorescence gel analysis of S. mutans biofilms also identified ilvE as being expressed differentially (48). Taken together, these findings suggest a role for amino acid biosynthetic genes in the acid stress response and could represent a pathway for the modulation of acid end products of fermentation.…”
mentioning
confidence: 67%
“…In that proteome analysis, performed by Len et al (39) and using conditions of acid stress, several genes involved in branched-chain amino acid biosynthesis were upregulated at pH 5.0, including ilvC, encoding a keto acid reductoisomerase, and ilvE, encoding a branched-chain amino acid aminotransferase. Two-dimensional fluorescence gel analysis of S. mutans biofilms also identified ilvE as being expressed differentially (48). Taken together, these findings suggest a role for amino acid biosynthetic genes in the acid stress response and could represent a pathway for the modulation of acid end products of fermentation.…”
mentioning
confidence: 67%
“…2D-DIGE was used to identify significant changes in 179 protein spots for E. coli in response to treatment with benzoic acid, a common food preservative that reduces the proton-motive force across the membrane (52). By comparing biofilm bacteria to planktonic cells, it was determined that Streptococcus mutans upregulates the synthesis of glucan (a component of plaque) and competence proteins while downregulating nucleotide biosynthesis, glycolysis, and central metabolism during biofilm growth (30). 2D-DIGE was also used to identify novel Helicobacter pylori Cag-associated proteins by comparing the proteomic profiles of wild-type Cag Ï© H. pylori and a cag pathogenicity island deletion strain (4).…”
mentioning
confidence: 99%
“…In this regard, Rathsam et al [9] showed that compared with 2D-GE proteome analysis, DIGE analysis resulted in a 3-fold increase in the number of identified protein spots that were significantly altered in their level of expression in biofilms formed by Streptococcus mutans. Additionally, we used an EDTA-based extraction method which resulted in higher protein yield than the vortexing method, which also likely contributed to the differences in protein profiles between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances in proteomics have allowed the identification of large-scale changes in protein profiles of biological systems, including microbial biofilms [9][10][11][12][13]. Recently, we performed proteomic analysis of cell walls of mature biofilms formed on catheter discs using two-dimensional difference-in-gel electrophoresis (DIGE), and showed that biofilm cell walls (as compared to planktonic cells) express differential levels of various proteins, including alcohol dehydrogenase (Adh1p) [14].…”
Section: Introductionmentioning
confidence: 99%